HUBUNGAN ANTARA RISIKO PENULARAN COVID-19 DENGAN TINGKAT ANSIETAS MAHASISWA/I ANGKATAN 2016 DI STIE YASA ANGGANA GARUT TAHUN 2020 - Ghassani Izlyn Fathara Sri Nadhiva (2020)
Anxiety is signal that represents existence of danger. Anxiety precipitation factor is a change in environmental situation, such as COVID-19 pandemic. Risk of COVID-19 transmission is considered an uncertain thing and can pose threat to community so that it can cause anxiety. This study aims to determine relationship between the risk of transmission of COVID-19 with the level of college students of 2016 year's generation anxiety at STIE Yasa Anggana Garut 2020. This study is an observational analytic study and uses cross sectional research design. Samples whom participated in this study were 113 respondents and simple random sampling technique was used. Data was collected using an online questionnaire and the research instrument used was Personal Risk Assessment related COVID-19 and Beck Anxiety Inventory. Univariate analysis results showed majority of students had a low risk of transmission of COVID-19 (53.1%) and mild anxiety levels (56.6%). Bivariate analysis results showed that there was a relationship between risk of COVID-19 transmission and anxiety levels (p-value: 0.001). Low level of risk is associated with good prevention knowledge and low level of anxiety associated with a low COVID-19 threat to students. Understanding about preventing transmission, anxiety, and its management needs to be given to students.